Re-Examining Alignment in a "Failed" L2 Autobiographic Research Interview. (April 2014) - Prior, Matthew T.
Contributing to a "social studies of interview studies, " this article addresses the treatment of "failed" autobiographic interviews. Taking a discursive constructionist approach, the author re-examines a problematic second language (L2) English interview with an immigrant man from Cambodia. Analysis focuses on the interactional management of (mis)alignment and how it contributed to the shape and outcome of the activity. By turning away from failure to accomplishment, and attending to the ways in which interviewee and interviewer use their differential linguistic and cultural expertise as topic and resource, the multi-layered activity takes on a new light that allows recognition of what was understood, shared, and ultimately achieved. The application of these insights for interview practice and analysis are discussed.